(untitled) (Applied Biological Research, 2024)
Siderophores are low molecular weight compounds secreted by bacteria that bind ferric iron with extremely high affinity. The siderophores help bacteria to meet their iron needs under stress conditions as these compounds help in the transport and storage of soluble form of iron in cells. In current study, we report the effect of various physicochemical parameters that influence siderophore production in marine Pseudomonas aeruginosa MGPB31. Siderophore production was assayed using Chrome Azurol S (CAS) shuttle assay. The maximum siderophore production (56% SU) was obtained in minimal M9 medium after 72 h incubation, followed by succinate medium (52% SU) and King’s medium (51% SU). The M9 medium was then modified by replacing its carbon, nitrogen and phosphate source. Enhanced siderophore production was observed in modified medium comprising of glycerol (70% SU), tri ammonium citrate (67% SU) and KH2PO4 (64% SU). The medium supplemented with iron exhibited a significant reduction in siderophore production. The effect of physical parameters like temperature, pH and agitation on siderophore production revealed that the isolate exhibited maximum siderophore production under static conditions in modified M9 medium devoid of iron at 25 ± 2°C and neutral pH. The enhanced siderophore production obtained by marine P. aeruginosa MGPB31 indicates its further applicability in fields of industry agriculture and environment.